Peningkatan Kemampuan Berpikir Kritis Anak Usia Dini Melalui Pembelajaran Sains - Wahdatul Umma; Sadaruddin Sadruddin; Andi Rezky Nurhidaya (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2025)
This study aims to improve the critical thinking skills of early childhood in Group B at TK Pabbata Ummi, Antang, Makassar through the implementation of a direct experiment-based science learning method. The main problem underlying this study is the children's low reasoning ability, passive learners, and the dominance of teacher-centered learning patterns. The method used is Classroom Action Research (CAR) following the Kemmis and McTaggart model, conducted in two continuous cycles. The research subjects consisted of 8 children, comprising 4 boys and 4 girls. Data collection techniques were carried out through structured observations using instrument sheets with four indicators of critical thinking, as well as authentic activity documentation methods. The collected data were analyzed using simple qualitative and quantitative descriptive methods. The results of the data analysis show a consistent and significant increase in the children's critical thinking skills. In the pre-cycle stage, the average classical achievement of the children was very low at only 12.50% (Not Yet Developing), which then increased to 32.81% (Starting to Develop) in Cycle I. After reconstructing the strategy by managing small groups and introducing more challenging science experiments (such as making lava bubbles), the average classical achievement in Cycle II jumped drastically to reach 87.50% (Developing Very Well). In addition to elevating the children's critical thinking skills in asking questions and solving problems, this study documented a positive accompanying impact in the simultaneous expansion of the children's new vocabulary mastery. The study concludes that concrete experiment-based science learning is highly effective in optimally improving early childhood critical thinking skills.